2010
DOI: 10.1249/mss.0b013e3181de2e4f
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ankle Taping on Knee and Ankle Joint Biomechanics in Sporting Tasks

Abstract: By limiting motion at the ankle, taping increased mechanical stability at this joint. Ankle taping also provided protective benefits to the knee via reduced internal rotation moments and varus impulses during both planned and unplanned maneuvers. Medial collateral and anterior cruciate ligament injuries may, however, occur through increased valgus impulse during sidestepping undertaken with ankle tape.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
25
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 36 publications
6
25
0
4
Order By: Relevance
“…This showed that the reverse-6 strips controlled the movement of the rearfoot effectively. The results of this present study agreed with that of Stoffel et al [15] and Vicenzino et al [16]. Analysing the data by groups, Fig.…”
Section: The Effect Of Low-dye Taping On Running Gaitsupporting
confidence: 93%
See 2 more Smart Citations
“…This showed that the reverse-6 strips controlled the movement of the rearfoot effectively. The results of this present study agreed with that of Stoffel et al [15] and Vicenzino et al [16]. Analysing the data by groups, Fig.…”
Section: The Effect Of Low-dye Taping On Running Gaitsupporting
confidence: 93%
“…However, Herradine et al [8] found that taping had no effect on rearfoot eversion during running. Stoffel et al [15] found that taping did not reduce the range of motion of the foot-ankle joint complex during sporting tasks. Although the efficacy of taping the foot remains questionable, taping continues to be advocated for use as a modality for injury management [7].…”
Section: Effects Of Tapingmentioning
confidence: 99%
See 1 more Smart Citation
“…The tasks were presented in a random order, accounting for any effect of any fatigue when the tasks are averaged across the individual. We have successfully used this approach previously in our sidestepping analysis (Besier et al, 2001, Cochrane et al, 2010, Dempsey et al, 2009, Stoffel et al, 2010. A successful trial involved participants taking off and successfully taking possession of the dropping ball and landing on their preferred foot on the force platform.…”
Section: Experimental Designmentioning
confidence: 99%
“…The moments were normalized to each subject's height (m) multiplied by their mass (kg) (Dempsey et al, 2009, Stoffel et al, 2010, Hewett et al, 2005, Yu et al, 2006, McLean et al, 2007, Chaudhari et al, 2005, Cochrane et al, 2010.…”
Section: Data Collection and Analysismentioning
confidence: 99%